A Packaged and Efficient SOEC System Demonstrator. (2nd June 2015) - Chatroux, André; Reytier, Magali; Di Iorio, Stéphane; Bernard, Charlotte; Roux, Guilhem; Petitjean, Marie; Mougin, Julie
Abstract : High Temperature Steam Electrolysis, based on solid oxide electrolysis cells (SOEC) is a promising way to produce hydrogen with high efficiencies. The balance of plant (BoP) is a key point for that technology because the heat management of the system has to be optimized to effectively reach the expected high electrical efficiency. For that purpose, the CEA-LITEN has designed and tested a packaged SOEC system demonstrator. It is based on a single 25-cell-stack and the required auxiliaries, including a steam generator at 150°C and high temperature exchangers to superheat the inlet steam flow thanks to the heat recovered in the exhaust gases. At 700°C, the system produces 1.2 Nm 3 /h of H2 with a total electrical consumption of 3.9 kWh/Nm 3, achieving 91% of efficiency, this efficiency corresponding to the higher heating value (HHV) of the produced hydrogen vs the electrical consumption of the system.